Age-Dependent Prognostic Effect by Mitosis-Karyorrhexis Index in Neuroblastoma: A Report from the Children's Oncology Group. (November 2014) - Teshiba, Risa; Kawano, Shinya; Wang, Larry L.; He, Lejian; Naranjo, Arlene; London, Wendy B.; Seeger, Robert C.; Gastier-Foster, Julie M.; Look, A. Thomas; Hogarty, Michael D.; Cohn, Susan L.; Maris, John M.; et al.
Prognostic effects of Mitosis-Karyorrhexis Index (MKI) used in the International Neuroblastoma Pathology Classification (INPC) are age-dependent. A total of 4, 282 neuroblastomas reviewed at the Children's Oncology Group Neuroblastoma Pathology Reference Laboratory (8/1/2001–3/31/2012) included 2, 365 low-MKI (L-MKI), 1, 068 intermediate-MKI (I-MKI), and 849 high-MKI (H-MKI) tumors. Cox proportional hazards models were fit to determine age cut-offs at which the relative risk of event/death was maximized in each MKI class. Backward-selected Cox models were fit to determine the prognostic strength of the age cut-offs for survival in the presence of other prognostic factors. The age cut-offs used in the INPC for L-MKI tumors (<60 months, n = 2, 710, 84.0% ± 1.0% event-free survival [EFS], 93.8 ± 0.7% overall survival [OS] vs ≥60 months, n = 195, 49.8% ± 4.6% EFS, 71.7% ± 4.1% OS; P < 0.0001) and I-MKI tumors (<18 months, n = 568, 83.8% ± 2% EFS, 93.7% ± 1.3% OS vs ≥18 months, n = 500, 51.4% ± 2.9% EFS, 66.7% ± 2.7% OS; P < 0.0001) were within the effective range for distinguishing prognostic groups. As for H-MKI tumors (no cut-off age in the INPC, 51.0% ± 2.2% EFS, 64.4% ± 2.1% OS), a new cut-off of 3–4 months was suggested (<4 months, n = 38, 82.3% ± 8.4% EFS, 81.8% ± 8.5% OS vs ≥4 months, n = 811, 49.6% ± 2.2% EFS, 63.7% ± 2.1% OS, P = 0.0034 and 0.0437, respectively). Multivariate analyses revealed that cut-offs of 60 and 18 months for L-MKI and I-MKI tumors, respectively, were independently prognostic. However, the cut-off of 4 months for H-MKI tumors did not reach statistical significance in the presence of other factors. The age cut-offs for MKI classes (60 months for L-MKI, 18 months for I-MKI, no cut-off for H-MKI) in the current INPC are reasonable and effective for distinguishing prognostic groups with increased risk of event/death for older patients.